Urban Design and the Role of Placemaking in Mainstreaming Nature-Based Solutions. Learning From the Biblioteca Degli Alberi Case Study in Milan - Boros, Judit; Mahmoud, Israa (Frontiers in Sustainable Cities, 2021)
Nature-based solutions' (NBS) relevance for tackling environmental challenges has been on the frontiers of urban regeneration mechanisms since the beginning of the 2010s. There is an increasing interest in applying NBS in urban planning and design to build support and engagement for sustainable urban development. However, NBS's operational use as deliberate design interventions is not widely reflected in the scientific discourse, more evidence is needed on how functional and viable aspects of urban nature can be conceptualized in urban design. This calls to explore the ways urban design can advance their understanding as part of place-specific, designed urban spaces. Through an ex-post analysis, the authors examined the design and implementation process of an exemplary NBS project, the Biblioteca degli Alberi park in Milan, part of one of the largest, recent urban regeneration projects in Europe. In a synthetic analysis, design drivers, enablers, and deficiencies are discussed, which affect the park's performance both from human-centered and nature-based perspectives. The park's case demonstrates design actions and considerations affecting all stages of the life-cycle of an NBS, from the creative design phase to the development, use, and management phases, and how urban design can create conditions for amplifying the multifunctional potential of urban ecosystems. The results highlight the importance of integrating an urban ecology perspective in the entirety of the design process when implementing NBS, consequently for a successful re-scoping of urban design and planning practices to infuse human-centeredness with 'nature-basedness.'